TRNSYS simulation of cooling system - Kum, Gary Jun Seng. (2013)
Singapore has been focusing on the energy-efficiency in the building in recent years. One good example will be the introduction of the Building Construction Authority (BCA) Green Mark Scheme. As most energy usage comes from the cooling system which is closed to 50%, much emphasis has been implemented on the proper implementation of the cooling system with the latest measure announced by the Senior Minister of State for Trade and Industry & National Development in the Parliament sitting during September 2012. In this project, a total of five types of cooling system were simulated using TRNSYS namely the vapor-compression, absorption, solar-absorption, solid desiccant with vapor-compression and solid desiccant with absorption. These cooling systems will be simulated on a typical office building model which is a 15-storey office building of 10,500 m2 floor area occupying 480 people as defined in TRNBuild and it is based on the Singapore Standard (SS) 553:2009. SS553:2009 is code of practice for air-conditioning and mechanical ventilation in buildings in Singapore. Simulation results from each individual cooling system will be compared with the vapor-compression cooling system so as to study on their feasibility. Furthermore, energy saving and economic assessment will be calculated and done respectively to select the most effective system. From these two results, the solid desiccant system with vapor-compression cooling was found to be the most techno-economical system which have about 20% energy saving and installation saving of 9% as compared with the vapor-compression cooling system.